Political Influence and the Dynamic Consistency of Policy - Garfinkel, Michelle R; Lee, Jaewoo (American Economic Review, 2000)
Garfinkel: Department of Economics, University of fornia, 3151 Social Science Plaza, Irvine, CA 92697; Lee: artment of Economics, University of California, 3151 SoScience Plaza, Irvine, CA 92697, and International MonFund, 700 19th Street, NW, Washington, DC 20431. We k, without implicating, Avinash Dixit, Amihai Glazer, chel Grossman, Luisa Lambertini, Stergios Skaperdas, an ymous referee, and seminar participants at the University alifornia-Los Angeles, California State Universityerton, and the 1998 Winter Meetings of the Econometociety for helpful comments on previous drafts of this r, which had been circulated under the title “Political ipline and the Dynamic Consistency of Policy.” The s expressed in this paper are those of the authors and ld not be attributed to the International Monetary Fund. See Torsten Persson and Guido Tabellini (1990) for a ul survey of this literature.